A Huge Splenic Cyst: Case Report (Journal of Surgical Sciences, 2019)
Splenic cyst is a relatively rare disease. They may occur secondary to trauma or even being more seldom due to parasitic infections, mainly caused by ecchinococcus granulosus. This patient had an atypical symptomatology, consisted mainly of fullness in the left upper abdomen and a palpable mass. Preoperative diagnosis was established with ultrasonography and computerized tomography. lmmunohistochemistry allows differential diagnosis between epidermoid and mesothelial cyst. For many years, open splectomy was the accepted treatment. Laparoscopic partial splenectomy is a procedure for the treatment of splenic cysts, because it cures the disease preserving the splenic tissue. Complete splenectomy is reserved for cases in which cyst excision cannot be done otherwise.Journal of Surgical Sciences (2012) Vol. 16 (2) : 101-105